Panelera sugar cane as a potentiator of the economy in Convención - Dulcey Nieves, Juan Pablo; CORONEL MONTAGUTH, YESSY LORENA (Universidad Francisco de Paula Santander, 2014)
This article presents scientific units resulting analysis allowed the construction of the Production ProfileTownship Convention. Leaving strategies involving structured opportunities in the labor market, and ground routes inclusion victim population, displacement and extreme poverty to economic development and job activity. The investigation failed to reveal e panela production as an activity which if addressed in the right way you will achieve a socioeconomic desararrollo Township. This is due to the historical characteristics of the crop, which has been present since the early twentieth century, and, when economic liberalization has allowed new markets to be exploited by producers of sugarcane will open. However, at present the certification issued by the INVIMA (Resolution 779 of 2006), is only fulfilled by less than 5.0% of the mills in the town which is not possible to use the economic situation, since the foreign market is demanding in terms of quality and production processes of the purchased items. Likewise, research is set in the context of the post-conflict being experienced Colombia, since production development in the framework of the law, allow the inhabitants to abandon illicit crop, which is used as an alternative income generating.